2020
DOI: 10.1002/cssc.201903281
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Nitrogen–Carbon Electrocatalysts for CO2 Reduction towards Syngas Generation

Abstract: Shifting syngas (an H2/CO mixture) production away from fossil‐fuel‐dependent processes (e.g., steam methane reforming and coal gasification) is mandatory, as syngas is of interest as both a fuel and as a value‐added chemical precursor. With appropriate electrocatalysts, such as silver‐based and metal–nitrogen–carbon (M‐N‐C) materials, the electrochemical CO2 reduction reaction (CO2RR) allows for the production of CO alongside H2 (from the hydrogen evolution reaction), and thus leads to syngas generation. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 117 publications
(328 reference statements)
1
36
0
Order By: Relevance
“…Therefore, utilizing a gas diffusion electrode (GDE), which was originally developed for fuel cell applications, for direct CO 2 delivery to the catalyst surface using water vapor as a carrier was proposed [84]. An article by Delafontaine et al reported that in a conventional H-type cell, the concentration of CO 2 in aqueous solution was 0.038 M. Direct delivery of humidified CO 2 to the flow cell resulted in a modest increase in the relative saturated CO 2 concentration to 0.041 M. In the same article, the diffusion coefficient of aqueous CO 2 was reported to be as low as 0.0016 mm 2 s −1 in CO 2 -saturated 0.1 M KHCO 3 [85,86]. Delivering humidified gaseous CO 2 with a GDE dramatically increased the CO 2 diffusion coefficient 10,000-fold to 16 mm 2 s −1 (Figure 10a) [86].…”
Section: Three-phase Boundarymentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, utilizing a gas diffusion electrode (GDE), which was originally developed for fuel cell applications, for direct CO 2 delivery to the catalyst surface using water vapor as a carrier was proposed [84]. An article by Delafontaine et al reported that in a conventional H-type cell, the concentration of CO 2 in aqueous solution was 0.038 M. Direct delivery of humidified CO 2 to the flow cell resulted in a modest increase in the relative saturated CO 2 concentration to 0.041 M. In the same article, the diffusion coefficient of aqueous CO 2 was reported to be as low as 0.0016 mm 2 s −1 in CO 2 -saturated 0.1 M KHCO 3 [85,86]. Delivering humidified gaseous CO 2 with a GDE dramatically increased the CO 2 diffusion coefficient 10,000-fold to 16 mm 2 s −1 (Figure 10a) [86].…”
Section: Three-phase Boundarymentioning
confidence: 93%
“…An article by Delafontaine et al reported that in a conventional H-type cell, the concentration of CO 2 in aqueous solution was 0.038 M. Direct delivery of humidified CO 2 to the flow cell resulted in a modest increase in the relative saturated CO 2 concentration to 0.041 M. In the same article, the diffusion coefficient of aqueous CO 2 was reported to be as low as 0.0016 mm 2 s −1 in CO 2 -saturated 0.1 M KHCO 3 [85,86]. Delivering humidified gaseous CO 2 with a GDE dramatically increased the CO 2 diffusion coefficient 10,000-fold to 16 mm 2 s −1 (Figure 10a) [86]. The ease with which gaseous CO 2 reached the catalyst resulted in a high CO 2 availability and a subsequent increase in the CO 2 RR partial current density.…”
Section: Three-phase Boundarymentioning
confidence: 93%
“…A more gaseous CO 2 has been reached at the catalyst, resulting in a large CO 2 availability and a consequent raise in the CO 2 R PCD. 24,47 Therefore, the usage of GDEs is the prominent strategy to increase the HCOO À PCD but it is very much challenging to avail a quick HCOO À production rate and a low overpotential with a high FE HCOOH .…”
Section: Gas Diffusion Electrode (Gde)mentioning
confidence: 99%
“…This is because the configuration can convert CO2 into products without the need for a liquid catholyte, so the cell resistance is very low, and a liquid catholyte circulation loop is not required [40]. Moreover, this minimizes any losses due to the dissolution of CO2 in the catholyte and results in an approximately 50% decrease in the power required to generate the same amount of CO with the same family of electrocatalysts as the flow cell [41,42]. This makes the zero-gap electrolyzer a promising configuration.…”
Section: The Zero-gap Electrolyzermentioning
confidence: 99%